The injury rate in NFL players increased following cancellation of preseason games because of COVID-19 - Baker, H. P.; Pirkle, S.; Cahill, M.; Reddy, M.; Portney, D.; Athiviraham, A. (Arthroscopy, Sports Medicine, and Rehabilitation, 2021)
Purpose: To investigate the injury rate in NFL athletes during the first four weeks of the 2020 NFL season. Methods: This study was a retrospective review of all NFL players who were placed on the injury report during the preseason and first fourweeks of the regular season from the 2016-2017 through 2020-2021 NFL regular seasons. Player`s date of injury was cross-referenced with an absence of statistics from the respective games for which they were ruled out to ensure accuracy. Injury rates were calculated per 1000 athletic exposures (AE). Relative risk (RR) with 95% 8confidence intervals (CI) compared injury rates between the two cohorts. Results: Over the course of the study period of four NFL seasons 3025 injuries were reported. Of the 3025 injuries reported, 582 (19%) occurred during weeks 1-4 of the 2020-2021 regular season, while 1292 (53%) occurred during preseason weeks 1-4 and 1151 (38%) during regular seasons weeks 1-4 of NFL seasons 2016-2017, 2018-2019, and 2019-2020. There was a significant increase in the injury rate during weeks 1-4 of the 2020-2021 regular season for all comparisons with the injury rate both during the preseason and regular season of three recent past NFL seasons. Conclusions: The rate of injury in NFL players during weeks 1-4 of the 2020-2021 regular seasons was significantly higher than three recent past NFL preseasons and regular seasons